LA SEGUNDA OPORTUNIDAD EN LA LEY CONCURSAL ESPAÑOLA - Sanz Sanz, Alberto (Revista de Derecho, 2020)
Act 25/2015, for the reformation of Bankruptcy Law modified the legal regime for the exemption of unfulfilled liabilities introduced by Act 14/2013. This reform is aimed at giving the debtor natural person, honest but unfortunate, a second opportunity for the exercise of business or professional activity, in order not to be forced to go to the informal economy. However, certain defects of legislative technique require the intervention of the judge, in order to properly interpret the law under a finalist criterion.